Congenital toxoplasmosis and pregnancy malaria detection post-partum: Effective diagnosis and its implication for efficient management of congenital infection. Issue 6 (December 2015) - Blay, Emmanuel Awusah; Ghansah, Anita; Otchere, Joseph; Koku, Roberta; Kwofie, Kofi Dadzie; Bimi, Langbong; Takashi, Suzuki; Ohta, Nobuo; Ayi, Irene
Abstract Congenital toxoplasmosis (CT) and pregnancy malaria (PM) have been individually reported to cause severe negative outcomes in pregnancies but the diagnostic method is still debatable. This study sought to estimate the prevalence of PM and CT single and co-infections in pregnant women by using various specimens including plasma and placental tissues. Genomic DNA extracted from the placenta, cord blood or blood of mothers was tested by PCR. Conventional method of immunodiagnosis was done for CT. We tested 79 pregnant women aged 18–42 years (mean: 28 ± 1.06). Prevalence of Plasmodium falciparum infection determined by PCR on mother's peripheral blood specimen was 6.3% whiles 57.3% was recorded for placental tissues (p < 0.01). PCR testing for placental tissues showed 29.2% positive for Toxoplasma gondii, whiles 76.0% of mothers had serum IgG against T. gondii. It should be noted that 6.3% of the placental tissues showed PCR positive for SAG 3, a marker of active infection in T. gondii. Although there were no enhanced foetal disorders at birth in our study, there is a possibility of active transmission of T. gondii from mothers to foetuses even in immune mothers. Our study suggests that foetuses were exposed to P. falciparum and T. gondii in utero, and placenta is a better specimen for PCR in detecting such episodes. In cases of PCR-positive samples, clinical follow-up after birth may be important.